Acute corneal edema without epithelium compromise. A case report and literature review (2017)
Acute corneal edema is caused by various factors, with different levels of severity, and various forms of presentation. This paper reports the case of a male patient presenting with acute corneal edema without epithelium compromise, whose clinical picture, ophthalmological examination and additional tests did not reveal its etiology. Also, a review of available literature was conducted looking for all known causes of acute corneal edema, which are classified according to the etiology of the corneal edema into injury or inflammation of the corneal epithelium or stroma, endothelial dysfunction or increase in intraocular pressure.